PENGARUH KOMITMEN ORGANISASI DAN PERCEIVED ORGANIZATIONAL SUPPORT TERHADAP TURNOVER INTENTIONS KARYAWAN PADA PT PLN (PERSERO) DISTRIBUSI JAWA TIMUR AREA SURABAYA UTARA - PRAFIDYA, HANIF (Jurnal Ilmu Manajemen (JIM), 2017)
Perceived organizational support and commitment in the employee aims to avoid turnover intentions, so that the vision can be achieved with good. This study aimed to analyze the influence of organizational commitment and perceived organizational support on employee turnover intentions. The sample used in this study was 50 permanent employees of PT PLN (Persero) Distribution of East Java, Surabaya Area North. The analysis technique in this study used multiple linear regression by using SPSS program version 18.0. These results indicate that individually variable organizational commitment significant negative effect on turnover intentions of employees at PT PLN (Persero) Distribution of East Java, Surabaya Area North and variable perceived organizational support individually significant negative effect on turnover intentions of employees at PT PLN (Persero) Distribution North Surabaya East Java Area. Simultaneously, organizational commitment and perceived organizational support significant negative effect on turnover intentions. Keywords: organizational commitment, perceived organizational support, turnover intentions.